Wayside Wifi-Repeater as a Railway Operation Facility for Optimizing Traffic Density Detection Cameras at Level Crossings - Wibowo, Agustinus Prasetyo Edy; Feryando, Dara Aulia; Winjaya, Fathurrozi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Wireless technology uses repeater mode as a medium for sending data to railway operation facility equipment and railway crossing density detection cameras. To cover a 225-meter track, three access points are needed, one as a server and two as repeaters. Testing includes coverage area with signal strength (RSSI), jitter, access point transfer, and data transmission. The test results show that the railway crossing area can be covered by a wireless repeater with an RSSI of 53.103 dBi. The jitter of the two access points, namely 28.65ms and 32.54ms, is included in the good category. When the access point is moved, there is an average packet loss of 2.6%. Data transmission at four points of the crossing track has a delay/latency of 38.49ms at point one, 66.03ms at point two, 45.33ms at point three, and 39.18ms at point four